Kinetic Modelling Of Lipase-Catalysed Flavour Esters Synthesis Focusing On Factor Affecting The Reaction Curves - Murugan, Thaatchayini (Universiti Sains Malaysia, 2021)
Flavour esters are high value compound due to higher demand in various industries. They can be produced via esterification and transesterification. The kinetics of lipase-catalyzed of flavour esters synthesis were investigated. The objectives of this work were to study the effect of substrate concentration on initial reaction rate and determine best reactor configuration for both Ping-Pong Bi-Bi and Ordered Bi-Bi models. Substrate concentration is one of the main factors in enzymatic reaction. Optimum concentration of each substrate needs to be evaluated in order to increase the reaction rate of flavour esters. Besides, selection of best acyl donor for isoamyl acetate production was studied based on the obtained initial rate; acetic anhydride was suitable for this ester formation. Apart from this, different acids with similar alcohol and vice versa also investigated in order to determine the substrate with inhibition effect and substrate which favored to increase the reaction rate. Furthermore, the kinetic data conclusively showed that CAL-B was catalytically more efficient than CRL for synthesis of butyl butyrate using butyric acid and butanol. Reactor configuration also studied for the bi-substrate models in lipase-catalyzed flavour esters synthesis, resulting batch reactor was suitable for Ordered Bi-Bi model whereas CSTR for Ping-Pong Bi-Bi model.